Penerapan Layanan Aplikasi Pegadaian Digital Service terhadap Kepuasan Nasabah di PT. Pegadaian CP. Medan Utama - Nabila Annisa Rahmadhani Siregar; Muhammad Irwan Padli Nasution (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
PT. Pegadaian is one of the state-owned companies that carries out credit financing on the basis of pawn law. PT. Pegadaian (Persero) is present and is one of the companies that follows and always innovates in technological developments. One of the innovations they made was to create a digital application, namely Pegadaian Digital Service (PDS). Pegadaian Digital Service (PDS) is a web and mobile-based digital service innovation to make it easier for customers to carry out all Pegadaian product transactions and can be accessed via gadget. This research uses a qualitative approach with descriptive methods. The aim of this research is to discuss how to implement Pegadaian Digital Service Application Services for Customer Satisfaction at PT. CP Pawn Shop. Main Field. The results of this research are that many customers feel this application is very effective and helps them in carrying out transactions, but there are also quite a few who are not yet interested in using the application. This is still subject to further evaluation and still needs to be improved.